Assessment of Citizens’ Knowledge, Attitudes and Behaviours toward Ecological and Environmental Problems in Morocco for Natural Resources Conservation and Sustainable Waste Management - Abderrazak, El-Alami; Abderrahman, Chait (Journal of agricultural, environmental and veterinary sciences, 2020)
Environmental behaviors are essential to ecological conservation and to environmental protection. The objective of this work was to assess knowledge and behaviors toward ecological and environmental problems, to determine the main environmental risks, and to purpose practical solutions for natural resources conservation and sustainable waste management in Morocco. The survey results revealed that rural villagers reported a higher level of ecological knowledge. Nevertheless, the inhabitants continue to overexploit natural resources to survive. They cut trees, transform natural habitats into cultivated land, put livestock into forest to graze, and capture and kill wild animals. The survey results revealed that the urban respondents reported a higher level of environmental knowledge. But a large fraction of the respondents do not use energy efficient light bulbs, do not have low flow water faucets, and do not separate household. In addition, they throw out hazardous materials in household waste, they discharge the expired and hazardous liquids to sewers and they do not reuse a fraction of domestic wastewater. Preliminary data collected on waste management systems showed that in rural areas the inhabitants reduce amounts of waste and reuse and recycle a large fraction of waste. Based on this study, we recommend several measures to encourage the conservation behaviors and the sustainable waste management. Because the mosques and the schools are the two main sources of environmental information, we highly recommend working on projects of Eco-Mosques and Eco-Schools.
Keywords: Environmental and ecological challenges; human behaviours; biodiversity protection; water and power conservation; waste management